Gestão de estoques em indústrias de fios têxteis - Souza, Flávio Avanci de (2009)
The inventory management is a relevant factor in the competitive present time of the textile market, since the necessity of cost reduction and invested capital is essential to the organizations survival. So the present research had the aim of raising information about the inventory management of the raw material, material in procedure and finished products in spinning in Paraná state with the purpose of proposing a list of items that contribute to the reduction of inventory. Therefore it is necessary to identify the main models and methods used in the inventory management, as well as identifying internal factors, external factors and organizational climate that influence in the inventory management. The technical procedure used was the research of data, accomplished by previously semi-structured questionnaires, sent to 5 spinning mills of the north and northeast of Paraná. Obtaining return of 3 questionnaires answered by the industrial units administrators. In conclusion, concepts of production administration are used; however there is the necessity of improvement and implementation of methods and tools that make possible continuous improvement in the management processes. Then, a list of items to be followed was prepared, of which the wanted results are the cost reduction, higher rentability and vitality of these companies.